HUBUNGAN PENGETAHUAN MANAJEMEN LAKTASI DAN DUKUNGAN KELUARGA TERHADAP PEMBERIAN ASI EKSKLUSIF DI PMB VITRI SUZANTI PALEMBANG - Sri Emilda; Reni Saswita (LPPM STIKes Mitra Adiguna, 2026)
The success of exclusive breastfeeding is influenced by several factors, particularly mothers’ knowledge of lactation management and family support. Adequate knowledge enables mothers to apply appropriate breastfeeding techniques, while family support enhances motivation and promotes the continuation of exclusive breastfeeding. This study aimed to analyze the relationship between lactation management knowledge, family support, and exclusive breastfeeding among mothers with infants aged 7–12 months at PMB Vitri Suzanti Palembang. This quantitative study employed a cross-sectional design and was conducted from January to February 2026. The study population consisted of 40 mothers with infants aged 7–12 months, and all participants were recruited using a total sampling technique. Data were collected through structured interviews using a questionnaire and analyzed using univariate and bivariate analyses with the Chi-square test at a significance level of ? = 0.05. The results showed that most respondents had good knowledge of lactation management (72.5%) and practiced exclusive breastfeeding (80.0%). Bivariate analysis revealed a significant relationship between lactation management knowledge and exclusive breastfeeding (p = 0.003), as well as between family support and exclusive breastfeeding (p = 0.020). In conclusion, both lactation management knowledge and family support are significantly associated with the successful practice of exclusive breastfeeding. Strengthening lactation management education and involving family members in breastfeeding counseling are recommended to improve exclusive breastfeeding rates in primary healthcare settings.